2014
DOI: 10.1016/j.schres.2014.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Wellness within illness: Happiness in schizophrenia

Abstract: Schizophrenia is typically a chronic disorder and among the most severe forms of serious mental illnesses in terms of adverse impact on quality of life. Yet, there have been suggestions that some people with schizophrenia can experience an overall sense of happiness in their lives. We investigated happiness among 72 outpatients with non-remitted chronic schizophrenia with a mean duration of illness of 24.4 years, and 64 healthy comparison subjects (HCs). Despite continued treatment with antipsychotic medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 69 publications
6
77
0
14
Order By: Relevance
“…In one, individuals with schizophrenia with a mean age in the 40's reported comparable levels of life satisfaction to healthy control participants, though the groups were not demographically matched complicating interpretation (Strauss et al, 2012). In another study involving elderly participants with schizophrenia and established illness (i.e., mean duration of illness over 20 years), patients were found to report significantly lower levels of happiness than healthy comparison subjects (Palmer et al, 2014). These studies, while informative about the level of subjective well-being in highly selected first-episode patients and more chronically ill samples, do not speak to the well-being of a large cohort of young adult outpatients with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…In one, individuals with schizophrenia with a mean age in the 40's reported comparable levels of life satisfaction to healthy control participants, though the groups were not demographically matched complicating interpretation (Strauss et al, 2012). In another study involving elderly participants with schizophrenia and established illness (i.e., mean duration of illness over 20 years), patients were found to report significantly lower levels of happiness than healthy comparison subjects (Palmer et al, 2014). These studies, while informative about the level of subjective well-being in highly selected first-episode patients and more chronically ill samples, do not speak to the well-being of a large cohort of young adult outpatients with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Data for the current study were drawn from an ongoing study of aging and schizophrenia conducted through the University of California, San Diego Center for Healthy Aging. We previously reported data on happiness in a smaller subsample from the ongoing project (Palmer et al, 2014); however, the present study is the first report on the association of several PPFs with objective biomarkers of health status. Diagnostic status was established with the semi-structured Clinical Interview for the DSM-IV-TR or DSM-5 (First, Spitzer, & Gibbon, 2002).…”
Section: Participantsmentioning
confidence: 70%
“…Given the negative outcomes associated with schizophrenia, it is perhaps not surprising that PPFs are rarely assessed or researched in this population. In an earlier report, our group examined individuals with chronic schizophrenia and found substantial heterogeneity in happiness levels of the sample (Palmer, Martin, Depp, Glorioso, & Jeste, 2014). Another study (Agid et al, 2012) showed that individuals with first-episode schizophrenia were as happy as control participants, despite their functional impairment.…”
Section: Introductionmentioning
confidence: 93%
“…Al respecto, la investigación del constructo felicidad como bienestar subjetivo se ha desarrollado en la psicología de la salud como un importante indicador de calidad de vida en muestras de pacientes crónicos en proceso de hemodiálisis (Bennet, Weinberg, Bridgman & Cummins, 2015;Musschenga, 1997), en personas de la tercera edad con diferentes diagnósticos médicos (Steptoe, Deaton & Stone, 2015) y en personas con esquizofrenia (Palmer, Martin, Deeep, Glorioso & Jeste, 2014).…”
Section: Tabla 2 Estadísticos Descriptivos De Las Variables Felicidadunclassified